A new HF-resistant tandem spray chamber for improved determination of trace elements and Pb isotopes using inductively coupled plasma-mass spectrometry - Krachler, Michael; Rausch, Nicole; Feuerbacher, Helmut; Klemens, Patrick (Spectrochimica acta. Part B, Atomic spectroscopy, 2005)
The use of a new HF-resistant tandem spray chamber arrangement consisting of a cyclonic spray chamber and a Scott-type spray chamber made from PFA and PEEK provides a straightforward approach for improving the performance of inductively coupled-mass spectrometry (ICP-MS). The characteristics of the tandem spray chamber were critically evaluated against a PEEK cyclonic and a PFA Scott-type spray chamber, respectively. Sensitivity across the entire mass range was increased by about three times compared to the conventional setup utilizing only one spray chamber. Precision of the results, especially at low signal intensities, improved by 160% and 31% compared to the cyclonic and Scott-type spray chamber, respectively. Using the tandem spray chamber, the oxide formation rate was lowered by about 50%. Signals as low as 30 counts could be determined under routine measurement conditions with a RSD of 2.4% thus allowing to precisely quantify small concentration differences at the ng l−1 concentration level. The excellent precision (0.02-0.07%) of 206Pb/207Pb and 206Pb/208Pb ratios determined in pore water samples was rather limited by the instrumental capabilities of the single collector ICP-MS instrument than by the performance of the tandem spray chamber.
Gesehen am 29.09.2020